1990
DOI: 10.1016/0735-1097(90)90283-u
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of double potentials in human atrial flutter: Studies during transient entrainment

Abstract: Double potentials, defined as atrial electrograms with two discrete deflections per beat separated by an isoelectric interval or a low amplitude baseline, have been observed during right atrial endocardial mapping of human atrial flutter. In this study, bipolar atrial electrograms were recorded during atrial flutter (mean cycle length 235 +/- 27 ms [+/- SEM]) from the high right atrium, the His bundle region, the coronary sinus and at least 30 right atrial endocardial mapping sites in 10 patients. Double poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(49 citation statements)
references
References 23 publications
3
46
0
Order By: Relevance
“…[12][13][14][15][16][17] In our study, the documentation of antidromic downstream activation confirmed their role as markers of local block. Wide double potentials separated by isoelectric intervals indicate local block under the recording catheter bipole, but they can be just adjacent to a conducting gap (ie, at its border) ( Figure 1); therefore, full mapping of the isthmus is necessary to identify the gap.…”
Section: Discussionsupporting
confidence: 52%
“…[12][13][14][15][16][17] In our study, the documentation of antidromic downstream activation confirmed their role as markers of local block. Wide double potentials separated by isoelectric intervals indicate local block under the recording catheter bipole, but they can be just adjacent to a conducting gap (ie, at its border) ( Figure 1); therefore, full mapping of the isthmus is necessary to identify the gap.…”
Section: Discussionsupporting
confidence: 52%
“…In patients with typical AFL, split potentials indicating a line of complete conduction block have been documented at the CT. 11,12 Although the barrier at the CT is considered anatomically fixed, mapping studies in animal models have shown transverse conduction across the CT in the normal heart. 10 Recent studies suggest there is a rate-dependent transverse conduction block at the CT in patients with typical AFL.…”
Section: Transverse Conduction Block Of the Ctmentioning
confidence: 99%
“…7,8 We evaluated the transverse conduction capability of the CT by RA extrastimulation from both a septal site and an anterior free wall site that were posterior anterior, respectively, to the CT. As demonstrated in the present study, extrastimulation with shorter coupling intervals resulted in split potentials and a marked alteration of the activation sequence, suggestive of a functional conduction block. 7,9,11,12,[25][26][27] The mechanism of the conduction block is very likely to be anisotropy rather than specific differences in local refractoriness. Anisotropy at the CT with a high conduction velocity in the longitudinal direction and a low conduction velocity in the transverse direction because of a high gap junction density at the end-to-end connections and a low density at the side-to-side connections is well known.…”
Section: Transverse Conduction Block Of the Ctmentioning
confidence: 99%
See 1 more Smart Citation
“…In typical human AFL, the wavefront propagates up the septal wall and down the free wall within the RA [3][4][5][6] and a line of block between the vena cavae plays a pivotal role in preventing the activation wavefront derived from short-circuiting between the septum and lateral wall in the RA, leading to maintenance of this reentry. 7,8 Double potentials recorded during AFL, which are thought to represent functional block, [9][10][11] have been frequently identified in broad areas along the vena cavae, [4][5][6]12 and from the results of previous mapping studies in humans the crista terminalis (CT) is generally considered to be the posterior boundary of the AFL circuit. 7,8,[13][14][15][16] However, it has been reported that AFL can have a lower reentrant loop in an isthmus-dependent manner.…”
mentioning
confidence: 99%